Membangun Etika Profesional Guru Pendidikan Agama Kristen : Tanggung Jawab terhadap Siswa di SMKN 2 Manokwari (Lembaga Pengembangan Kinerja Dosen, 2025)
Christian Religious Education (PAK) teachers have an important obligation in building students' personalities through the process of teaching Christian values ​​that reflect the life of Jesus Christ. The study discusses building professional ethics of Christian Religious Education teachers: responsibility towards students at SMKN 2 Manokwari, specifically teachers are responsible for students. PAK teachers do not only teach knowledge; but must provide moral and spiritual examples, foster students so that they grow in faith in Jesus, with values ​​(love, justice and equality). Building ethics as a guideline to become role models and teacher professionalism is very important, this study uses a qualitative descriptive method. All PAK teachers have their responsibilities to be responsible for themselves as professionals, moral examples related to the social community and at school effectively, with intellectuals to study teaching materials thoroughly, and moral responsibility and examples of faith. The teacher's code of ethics in any situation can overcome conflict problems with students or parents in order to ensure that learning can run well. The results of this analysis indicate that experienced PAK teachers can create a classroom atmosphere by encouraging students to grow in good character. By having the quality of Christian faith in the existing environment, Education not only improves students' ability to learn, but students can be closer to God. This can ensure that students change morally and spiritually in accordance with Christian teachings, building the professional ethics of PAK teachers at SMKN 2 Manokwari to be important and alive.